Factors Influencing the Adoption of QRIS Digital Payments in MSMEs - Anaya Zahra Santika; Ayatulloh Michael Musyaffi; Gentiga Muhammad Zairin (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This study examines factors influencing the adoption of QRIS digital payments in MSMEs in West Jakarta. QRIS (Quick Response Code Indonesian Standard) standardises QR codes for easier transactions. Utilising the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, this research investigates the impact of Performance Expectancy, Effort Expectancy, and Financial Literacy on Behavioural Intention to use QRIS. Data were collected via a survey of MSME owners using QRIS and analysed with SmartPLS software using the Partial Least Squares (PLS) method. Findings indicate that Performance Expectancy, Effort Expectancy, and Financial Literacy significantly influence Behavioural Intention. This research contributes to understanding digital payment technology adoption among MSMEs and provides insights for policy development to boost QRIS use. Future research should expand geographic coverage, sample size, and explore additional financial technologies to understand adoption challenges and opportunities more comprehensively.